{2-Morpholino-N- 1-(2-pyridyl)ethylidene ethanamine-kappa N-3,N ',N ''}bis(thiocyanato-kappa N)zinc(II) - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H.; Hisham, N.A.I. (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, [Zn(NCS)(2)(C13H19N3O)], contains two crystallographically independent molecules. In each molecule, the Zn-II ion is five-coordinated by the N,N',N ''-tridentate Schiff base and the N atoms of two thiocyanate ligands in a distorted square-pyramidal geometry. The two molecules differ mainly in the deviations from the ideal geometry, with tau values of 0.14 and 0.33. In the crystal, intermolecular C-H center dot center dot center dot S hydrogen bonds are observed. An intramolecular C-H center dot center dot center dot N hydrogen bond occurs in one of the independent molecules.